The Fonthill Dental Surgery Complication Classification Scale - Peter C. Fritz; Amanda B. Longo (Wiley, 2019)
Abstract Objectives A lack of consensus on how to classify post‐operative complications in dentistry limits the ability for comparison of outcomes among treatments and their primary providers. Therefore, the Fonthill Dental Surgery Complication Classification Scale has been proposed as a uniform reporting tool to allow for the standardized quality assessment of dental treatment. This instrument classifies negative outcomes arising after dental treatment and is based on the clinician and the clinician time required to resolve the complication in seven classes of increasing severity. Materials and Methods The scale was evaluated in a cohort of 2,382 consecutive patients, of which 9% experienced a complication, the majority of which were Class I or Class II-resolved without intervention by the dental surgeon. Results Four scenarios where interpretation of the scale was required are presented with an explanation of their complication class. Conclusions This classification system will ultimately prove reliable in measuring clinician success rate and aiding in the decision‐making process for patients, clinicians, and financial providers.